Personal Identifiable Information Erasure in Large Language Models in a Globalized Context : A Review from the Theoretical Perspective of Ulrich Beck's Risk and Reflexive Modernity (2024)
ABSTRACT: This review presents the trajectory and current scenario regarding the collection and processing of digital Personally Identifiable Information and its influence on the development of Artificial Intelligence applications such as Large Language Models. From this context, the state of existing legislative frameworks in the European Union, the State of California in the United States, and Colombian legislation in relation to the handling of personal data in technologies that use Artificial Intelligence is evaluated. At the same time, the frameworks for data processing by technology companies that have developed the most popular LLMs for the period between 2023 and 2024 are reviewed. This review aims to analyze, from the perspective of Ulrich Beck's risk society and reflexive modernization, how the uncertainties arising from the side effects produced by technological developments with global reach, such as LLMs, are presented.